Constructivism in Kant’s theoretical philosphy - Roberto Horácio de Sá Pereira (Humanities & Social Sciences Communications, 2022)
Abstract We set forth what one may call a “constitutional reading” in opposition to the traditional widespread “constructivist reading” of the object of cognition. In the light of the so-called one-object view reading of Transcendental idealism, the object of cognition is nothing but the object that exists in itself insofar as it appears to our cognitive apparatus. The object exists mind-independently, while our cognition of the same object must be mind-independent. The constructivist reading mistakes the epistemological problem of how we come to cognize mind-dependently that what we represent (“the constitutional view”) are mind-independent objects with the Berkelian ontological problem of how we construct objects out of an undifferentiated, unstructured manifold (the constructivist view) My diagnosis is as follows. The first reason is the traditional “two-worlds view” reading of Kant’s idealism: if we take what exists in itself and the object of cognition as distinct things, then we must conclude that the object of cognition is a mind-dependent construction. Constructivist readers mistake the mind-dependent nature of our human cognition of objects for the putative mind-dependent nature of the known object. The second reason is overintellectualization. Constructivist readers mistake the objectifying syntheses of the imagination, below the threshold of self-consciousness, for cognitive conceptual operations by means of which we cognize (erkennen) the objects of cognition, or so I shall argue.